2011
DOI: 10.1208/s12248-011-9308-3
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Modeling of Sequence-Dependent Antitumor Activity of Insulin-like Growth Factor Blockade and Gemcitabine

Abstract: Abstract. Agents that block insulin-like growth factor (IGF) signaling are under investigation in clinical trials. Antitumor effects are likely to be enhanced when combined with other agents, but administration sequence effects on activity are not well-described. Three breast cancer cell lines (MCF-7, MDA-MB-231, and Hs-578T) were treated with Gemcitabine and small molecule receptor tyrosine kinase inhibitor cis-3-[3-(4-methyl-piperazin-l-yl)-cyclobutyl]1-(2-phenyl-quinolin-7-yl)-imidazo [1,5-a]pyrazin-8-ylami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
(22 reference statements)
1
5
0
Order By: Relevance
“…Here, the synergistic killing effect may be due to violation of the balance between cell survival and cell death induced by DNA damage (gemcitabine) along with inhibition of the survival machinery of the cells (AEW541). In accordance with our results, in vitro studies in MCF7 cells reported effectiveness when using a selective IGF1R tyrosine kinase inhibitor (PQIP) in combination with gemcitabine [38]. Finally, enhancement of the response to other IGF1R monoclonal antibodies by gemcitabine has been demonstrated in several cancers, including breast tumors [39,40].…”
Section: Discussionsupporting
confidence: 89%
“…Here, the synergistic killing effect may be due to violation of the balance between cell survival and cell death induced by DNA damage (gemcitabine) along with inhibition of the survival machinery of the cells (AEW541). In accordance with our results, in vitro studies in MCF7 cells reported effectiveness when using a selective IGF1R tyrosine kinase inhibitor (PQIP) in combination with gemcitabine [38]. Finally, enhancement of the response to other IGF1R monoclonal antibodies by gemcitabine has been demonstrated in several cancers, including breast tumors [39,40].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, in vitro studies in MCF7 cells reported that the effectiveness of using the highly potent and selective IGF1R tyrosine kinase inhibitor PQIP, an analogue of OSI-906, in combination with chemotherapy (i.e. gemcitabine) depends on the sequence of drug administration (Khatri et al 2012). Enhancement of the response to the IGF1R mAbs AVE1642 or BMS-754807 by gemcitabine has been demonstrated using established BxPC-3 human pancreatic tumor xenografts (Maloney et al 2003, Awasthi et al 2012, suggesting that these types of IGF1R and chemotherapy combination therapies may also have clinical benefit in other cancers including breast.…”
Section: Igf1r and Chemotherapymentioning
confidence: 99%
“…To the best of our knowledge, there have been some examples which take advantage of the established PK/PD models and the estimated parameters to perform simulations based on designed administration schedules. By comparing the predicted drug response of different administration schedules, the modeling approach can realize the optimization of the combination use of anticancer drugs and show preferable predicting prospect in both preclinical and clinical field …”
Section: Introductionmentioning
confidence: 99%